Spain : Selected Issues. (IMF Staff Country Reports; Country Report, 2017)
This Selected Issues paper analyzes the challenges for the Spanish pension system. Spain's population, like those in many other advanced economies, is projected to age over the coming decades. Although projections are uncertain, the simple fact is that Spain's aging and shrinking population has put and will continue to put relentless pressure on contributory pension finances. The reforms adopted in 2011 and 2013 if fully implemented will ensure the financial viability of the contributory pension system. A package of reforms could include parametric changes such as automatically linking the retirement age to changes in life expectancy and adjusting accrual rates and the calculation of pensionable earnings.